THE EFFECT OF HAND-ARM VIBRATIONS ON DISTAL FOREARM BONE MINERALISATION - Filipović, Tamara (Medical Research, 2023)
Prolonged, mainly professional, exposure to hand-arm vibration (HAV) may cause a complex chronic disorder of the upper extremities known as Hand-Arm Vibration Syndrome (HAVS). Besides vascular and neurological injuries, such exposure to HAV may cause various bone disorders in the form of cystic changes, exostoses, aseptic necrosis, osteoarthritis, spontaneous fractures and osteoporosis. The objective of this study was to examine whether there are changes in the bone mineral density in the distal forearm in persons professionally exposed to HAV. In a group of 31 workers professionally exposed to vibrations (29 men and 1 woman) with neurological and/or vascular signs of HAVS, the bone mineral density of the distal part of the radius of both hands was examined by dual X-ray absorptiometry (DXA). The control group consisted of 25 healthy subjects with no history of HAV exposure. Osteopenia was found in 14 subjects (45.16%), which makes a statistically significant difference compared to the control group (p=0.017), where osteopenia was found in 3 subjects (12.0%). Osteoporosis was not found in any of the subjects. Analyzing the value of T score for the dominant (-0.81±0.58 SD) and non-dominant hand (-0.62±0.68SD) in our patients, we found no statistically significant difference in the average T score values of the dominant and non-dominant hand (p=0.269). Changes in bone density at the distal radius are common in persons occupationally exposed to HAV. Distal forearm DXA examination in workers occupationally exposed to HAV can help diagnose HAVS.